Affective symptoms in multiple system atrophy and Parkinson's disease: response to levodopa therapy. Issue 4 (1st April 1999) - Fetoni, V; Soliveri, P; Monza, D; Testa, D; Girotti, F
Abstract : The objective was to determine the extent to which psychiatric disturbances (especially mood disorders) generally considered poor prognostic factors, are present in patients with striatonigral (SND) type multiple system atrophy (MSA) compared with patients with idiopathic Parkinson's disease (IPD). The Hamilton depression scale (HAM-D), brief psychiatric rating scale (BPRS), and Unified Parkinson's disease rating scale (UPDRS) were administered to clinically probable non-demented patients with SND-type MSA and patients with IPD matched for age and motor disability, at baseline and after receiving levodopa. At baseline total HAM-D score was greater in patients with IPD. Overall, BPRS score did not differ between the two groups; however, patients with IPD scored higher on anxiety items of the BPRS, and patients with MSA had higher scores on the item indicating blunted affect. After levodopa, both groups improved significantly in UPDRS and HAM-D total scores (just significant for patients with MSA). Patients with IPD improved significantly in total BPRS score but patients with MSA did not. At baseline patients with IPD were more depressed and anxious than patients with MSA who, by contrast, showed blunted affect. After levodopa, depression and anxiety of patients with IPD improved significantly whereas the affective detachment of patients with MSA did not change. Major neuronal loss in the caudate and ventral striatum, which are part of the lateral orbitofrontal and limbic circuits, may be responsible for the blunted affect not responsive to levodopa therapy found in patients with MSA.